2022
DOI: 10.1177/09544054221111896
|View full text |Cite
|
Sign up to set email alerts
|

An insight on Powder Mixed Electric Discharge Machining: A state of the art review

Abstract: Electrical discharge machining (EDM) is an exigent focus of interest for researchers since its inception. EDM has a wide range of applications due to its non-contact machining process based on the spark erosion method. EDM is a non-conventional machining process with high potential in the recent industrial era. Due to the few limitations of EDM, many hybrid techniques are evolved in recent years. The present review paper elucidates the in-depth mechanism of the material removal process in EDM. Hybrid EDM proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 203 publications
(313 reference statements)
0
3
0
Order By: Relevance
“…Micro cracks developed at higher pulse on time and peak current values due to an increase in discharge energy [20]. The increment in impulsive forces and discharge energy, which is a function of current and pulse on time, results in the removal of more material, thereby generating larger craters.…”
Section: Parameters Affecting the Surface Crack Densitymentioning
confidence: 99%
“…Micro cracks developed at higher pulse on time and peak current values due to an increase in discharge energy [20]. The increment in impulsive forces and discharge energy, which is a function of current and pulse on time, results in the removal of more material, thereby generating larger craters.…”
Section: Parameters Affecting the Surface Crack Densitymentioning
confidence: 99%
“…It can be observed that MRR and SR values were improved by using both nanopowders. This was because the addition of nanopowders enlarged the thermal conductivity of the dielectric, increased the discharge gap, decreased the breakdown strength, and enhanced the spark difference [60][61][62]. It also facilitated the proper flushing of eroded particles [63].…”
Section: Optimizationmentioning
confidence: 99%
“…It was pointed out from the experimental results that vegetable and bio-oil-based dielectrics have great potential to replace traditional dielectrics, thus providing a more sustainable manufacturing process in the future. Tapas 17 checked the Feasibility of jatropha oil as a dielectric fluid. Dissolved gas analysis proved that transesterified Jatropha oil provides sustainable and biodegradable dielectrics for EDM.…”
Section: Introductionmentioning
confidence: 99%